2022
DOI: 10.1007/s00404-022-06442-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-200 family as predictive markers during systemic therapy of metastatic breast cancer

Abstract: Purpose Circulating miRNAs can provide valid prognostic and predictive information for breast cancer diagnosis and subsequent management. They may comprise quintessential biomarkers that can be obtained minimally invasively from liquid biopsy in metastatic breast cancer patients. Therefore, they would be clinically crucial for monitoring therapy response, with the goal of detecting early relapse. This study investigated miRNA expression in patients with early and/or late relapse, and the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…The present study enrolled 47 patients with MBC. Patient and tumor characteristics have been reported in a previous article and can be found in the supplementary material (Supplementary Material, Table S1 ) [ 30 ]. At study entry, on average, participants were 57 years old (Range: 35–89).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study enrolled 47 patients with MBC. Patient and tumor characteristics have been reported in a previous article and can be found in the supplementary material (Supplementary Material, Table S1 ) [ 30 ]. At study entry, on average, participants were 57 years old (Range: 35–89).…”
Section: Resultsmentioning
confidence: 99%
“…Blood plasma sampling, cell-free RNA isolation as well as cell-free miRNA detection were performed as described previously [ 30 ]. The expression levels of miR-200a, miR-200b, miR-200c, miR-141, and miR-429 were measured, respectively, at the three following consecutive time points in the plasma of 47 patients with MBC: (1) at baseline before the start of a new line of systemic therapy (BL, miRNA BL ), (2) after the first completed cycle of a new line of systemic therapy (1C, miRNA 1C ), and (3) at the radiologically confirmed progression of the disease (PD, miRNA PD ).…”
Section: Methodsmentioning
confidence: 99%
“… MiR-200: this is a miRNA that is involved in the invasion and metastasis of breast cancer through the regulation of EMT (epithelial-mesenchymal transition) processes. Increasing miR-200 expression has been shown to reduce the ability of cancer cells to invade and migrate, making it a potential therapeutic target [ 183 , 184 ]. MiR-10b: it has been shown that miR-10b is involved in the metastasis of breast cancer through the regulation of EMT processes.…”
Section: The Role Of Mirnasmentioning
confidence: 99%
“…High levels of circulating miR-200c and miR-141 were associated with the poor OS of colon cancer patients [ 30 ]. Circulating miR-200 family members could predict OS and PFS in patients undergoing systemic therapy for metastatic breast cancer [ 31 ]. High levels of miR200 family members were strongly associated with reduced OS and PFS [ 31 ].…”
Section: Mir-200 Family As a Diagnostic And Prognostic Markermentioning
confidence: 99%
“…Circulating miR-200 family members could predict OS and PFS in patients undergoing systemic therapy for metastatic breast cancer [ 31 ]. High levels of miR200 family members were strongly associated with reduced OS and PFS [ 31 ]. These reports indicate that the miR-200 family could serve as both diagnostic and prognostic markers.…”
Section: Mir-200 Family As a Diagnostic And Prognostic Markermentioning
confidence: 99%